2011
DOI: 10.4314/wsa.v37i2.65871
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of flow through free double baffled gates

Abstract: Studying the flow patterns and behaviour of double baffled gates under different flow heads is important to improve their performance, which could help in widening the range of their application. In the present study, physical and numerical investigations were conducted on the double baffled gate. A 3D Acoustic Doppler Velocity Meter (ADV) was used for laboratory measurements of the instantaneous velocity fields in the physical gate model. In parallel with this, the CFD Fluent package was adopted to carry out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Use of finite-element analysis began with McCorquodale and Li (1971), who considered flow under a sluice gate. Many other studies have since appeared in the literature, including those reported by Bhajantri et al (2007aBhajantri et al ( , 2007b, Castro-Degado (1986), Chan et al (1973), Chanel and Doering (2008), Daneshmand and Kazemzadeh-Parsi (2004), Guayjarernpanishk andAsavanant (2009), Helmi andEl-Gamal (2011), Ikegawa and Washizu (1973), Li et al (1989), Petrila (2002), Sankaranarayanan and Rao (1996) and Vanden-Broek (1997).…”
Section: Introductionmentioning
confidence: 90%
“…Use of finite-element analysis began with McCorquodale and Li (1971), who considered flow under a sluice gate. Many other studies have since appeared in the literature, including those reported by Bhajantri et al (2007aBhajantri et al ( , 2007b, Castro-Degado (1986), Chan et al (1973), Chanel and Doering (2008), Daneshmand and Kazemzadeh-Parsi (2004), Guayjarernpanishk andAsavanant (2009), Helmi andEl-Gamal (2011), Ikegawa and Washizu (1973), Li et al (1989), Petrila (2002), Sankaranarayanan and Rao (1996) and Vanden-Broek (1997).…”
Section: Introductionmentioning
confidence: 90%
“…However, the depth of scour hole, dune height, volume of scour, extent of scour, and dune are maximum, when flow is completely above the gate and minimum when completely below the gate. [23] Presents an experimental investigation and numerical analysis of the flow through the free double baffled gate. It was found that the gate inclination angle (α) and the gate spacing (S) are the most effective parameters in controlling the H-Q relation, where (Q is the discharge throughout the gate and H is the upstream head of the gate measured vertically from the crest (in the case of pure weir flow).…”
Section: Introductionmentioning
confidence: 99%